Economic impact of open source on small business : a case study - Henderickson, Mike (O'Reilly Media, 2012)
Open source is not only a catalyst for small business growth, but also a driver of future success for many startups today. Bringing together Bluehost anonymized customer data and trends with O'Reilly Media's job market data, along with other sources of trend data, this report captures the current state of open source as it relates to small to medium-sized businesses.